An activity-friendly environment from the adolescent perspective: a concept mapping study - L. M. Hidding; M. J. M. Chinapaw; T. M. Altenburg (BMC, 2018)
Abstract Background In today's society, few adolescents meet physical activity guidelines and effects of physical activity promoting programmes are disappointing. In studies exploring determinants of physical activity, the perspective of adolescents themselves is largely lacking. Also, there is a lack of knowledge on potential environmental determinants of adolescent physical activity. Therefore, this study aimed to explore adolescents' perspectives on characteristics of an activity-friendly environment. Methods Concept mapping meetings were conducted with four secondary school classes, including 115 adolescents (13-17 years). Each student generated ideas regarding the characteristics of an activity-friendly environment. For each school class, ideas were combined and identical ideas were removed. Next, students individually sorted all ideas, based on self-perceived similarity, and rated their importance on a five-point Likert-scale. A concept map was created for each school class using multidimensional scaling and hierarchical cluster analysis. Finally, the researchers named the potential environmental determinants within the clusters. Results The concept maps depicted 23 unique potential determinants of activity friendliness, of which 15 were similar across all school classes. Potential determinants were categorized in the physical-, social-, economic-, and motivational domain. The most frequent and important adolescent-perceived determinants of activity friendliness across all school classes belonged to the physical domain, e.g. a suitable area including a proper surface for a variety of sports, and good lighting in the playground. Conclusions Our findings show that adolescents perceive potential determinants in the physical and economic domain as most important for activity friendliness, indicating that future interventions might benefit from targeting potential determinants within these domains.